Effect of Rifampin on the Growth of Bacteriophage T5 - Beck Man, L. David (1972)
A rifampin-resistant mutant of Escherichia coli F with an altered ribonucleic acid (RNA) polymerase was isolated and was shown to support the growth of phage T5 in the presence of rifampin. In contrast, wild-type, rifampin-sensitive cells of E. coli F did not support the growth of T5 in the presence of rifampin. We concluded, therefore, that no phage-specific RNA polymerase is essential to the development of phage T5. Rather, the host RNA polymerase, or at least that portion of the host RNA polymerase that is responsible for rifampin sensitivity, is required for the transcription of all essential regions of the T5 deoxyribonucleic acid. These conclusions are supported by in vitro measurements of the rifampin sensitivity of the RNA polymerase activities extracted from infected and uninfected cells. The rifampin sensitivity of the RNA polymerase activity extracted from uninfected cells was similar to the rifampin sensitivity of the RNA polymerase activity extracted 30 min after infection.